Biology and Ecology of Edible Marine Gastropod Molluscs - Santhanam, Ramasamy (Milton : Apple Academic Press, 2018)
"This comprehensive volume, Biology and Ecology of Edible Marine Gastropod Molluscs, focuses exclusively on sea snails or gastropods, which are popular food items and occupy an important role as commercial shell craft industry. Familiar examples include conchs (highly sought after due to their mild flavor) as well as escargot, abalone, and periwinkle snails. This book covers the profile (habitat, distribution, morphology, food and feeding, reproduction, conservation status, etc.) of about 180 species of commercial edible marine gastropod molluscs as well as their nutritional values, commercial importance, and pharmaceutical value. Also included is information on their prevalent diseases and parasites. The informative descriptions are presented in an easy-to-read style with neat illustrations. This volume, in the Biology and Ecology of Marine Life book series, will be of great use for the students and researchers of disciplines such as fisheries science, marine biology, aquatic biology and fisheries, and zoology. It will also be a valuable reference book for the libraries at universities, schools, and scientific institutions."--
Intro; Halftitle Page; Title Page; Copyright; Table of Contents; List of Abbreviations; Preface; 1 Introduction; 2 Biology and Ecology of Edible Marine Gastropod Molluscs; 3 Profile of Edible Marine Gastropod Molluscs; 4 Nutritional Value of Edible Marine Gastropod Molluscs; 5 Pharmaceutical Value of Edible Marine Gastropod Molluscs; 6 Industrial Uses of Edible Marine Gastropod Molluscs; 7 Aquaculture of Edible Marine Gastropod Molluscs; 8 Diseases and Parasites of Edible Marine Gastropod Molluscs; References; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Life Sciences / Biology / Marine Biology; SCIENCE / Life Sciences / Zoology / General